2019
DOI: 10.3390/app9153191
|View full text |Cite
|
Sign up to set email alerts
|

Differential Efficacy of Two Dental Implant Decontamination Techniques in Reducing Microbial Biofilm and Re-Growth onto Titanium Disks In Vitro

Abstract: Dental implants are crucial therapeutic devices for successful substitution of missing teeth. Failure cases are mainly pathogen-associated events, allowing clinical progression toward peri-mucositis or peri-implantitis. The aim of this study was to compare the performance of two mechanical decontamination systems, Nickel-Titanium brush (Brush) and Air-Polishing system with 40 µm bicarbonate powder (BIC-40), by means of a novel bioluminescence-based model that measures microbial load in real time. Briefly, 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It has been shown that sandblasting with aluminum oxide particles with a diameter between 100 and 150 microns favors better osseointegration; the irregular surface increases the osteoconductivity of the metal, otherwise inert, favoring the adhesion and the activity of the osteoblasts. As a result, healing of the bone-implant interface is faster [ 47 ].…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…It has been shown that sandblasting with aluminum oxide particles with a diameter between 100 and 150 microns favors better osseointegration; the irregular surface increases the osteoconductivity of the metal, otherwise inert, favoring the adhesion and the activity of the osteoblasts. As a result, healing of the bone-implant interface is faster [ 47 ].…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…Considering its abrasive nature, nowadays, low abrasive agents such as glycine and erythritols are commonly used [ 5 ]. However, in vitro studies pertaining to usage of NaHCO 3 on Titanium disc has shown promising results as an air abrasive [ 55 , 56 ].…”
Section: Air Abrasive Powdersmentioning
confidence: 99%
“…Furthermore, Ti6Al4V is commonly used in the biomedical field due to its high biocompatibility [ 11 , 12 ], such as artificial hip joints, compression hip screws, dental implants body, bone plate, heart catheter, artificial heart valve for orthodontic surgery, etc. [ 13 , 14 , 15 , 16 , 17 ]. Furthermore, low surface roughness is usually required to obtain superior functionality for most of its applications, such as implants and turbine blades [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%